Making public theology operational: public theology and the church - Oorschot, Frederike van (International journal of public theology, 2019)
This article examines how public theologians aim to bring their theology into the practice of the church. In the first part it analyses the references to the church in the work of contemporary public theologians from the United States and Germany and suggests four different categories for the relations explored (explicit function, implicit function, public church, church as public). In the second part, it discusses three systematic aspects of these relations. First, following Kuyper, it defines the term church' more accurately. Second, it offers insights into liturgical research in order to help to sharpen the places where and means by which the implicit shaping of individual ethical behaviour in the church takes place, as exemplified in the work of Dirk Smit. Third, it discusses the task of pastors as mediators between church and theology.